2020
DOI: 10.1002/ppul.25052
|View full text |Cite
|
Sign up to set email alerts
|

Do pulmonary and extrapulmonary features differ among cystic fibrosis, primary ciliary dyskinesia, and healthy children?

Abstract: Background: Primary ciliary dyskinesia (PCD) is generally likened to cystic fibrosis (CF) due to similarities in impaired mucociliary clearance and some other symptoms. The aim of our study was to investigate pulmonary and extrapulmonary characteristics of children with CF and PCD since no studies have addressed respiratory muscle strength in children with PCD and to compare the results to those obtained from healthy age-matched controls. Methods: Pulmonary and extrapulmonary characteristics were assessed by 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 42 publications
4
13
2
Order By: Relevance
“…The patients with PCD had lower completed steps (86 vs. 90 steps) at the end of the test in the present study. A few studies previously evaluated exercise capacity in patients with PCD and the findings are contradictory 3–7 . Similar to our results, Sonbahar‐Ulu et al, Simşek et al, and Madsen et al reported decreased exercise capacity in PCD patients than healthy controls.…”
Section: Discussionsupporting
confidence: 78%
“…The patients with PCD had lower completed steps (86 vs. 90 steps) at the end of the test in the present study. A few studies previously evaluated exercise capacity in patients with PCD and the findings are contradictory 3–7 . Similar to our results, Sonbahar‐Ulu et al, Simşek et al, and Madsen et al reported decreased exercise capacity in PCD patients than healthy controls.…”
Section: Discussionsupporting
confidence: 78%
“…Additionally, some studies provided additional details, that is, Kinghorn et al included those who had FEV1 > 60% with no cough or wheeze in the last 2 weeks; Denizoglu Kulli et al excluded those with any hospitalization in the last 1 month or with a history of cardiovascular disease; Magnin et al excluded anyone with an acute exacerbation in the last 6 weeks, however, included some who were toward the end of 2 weeks antibiotics course. In five studies, PCD was diagnosed using transmission electron microscopy (TEM) and genetic testing 32–34,38,39 . In the remaining three studies, TEM along with clinical phenotype formed the basis of diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…All eight studies included in this systematic review were observational studies 32–39 . Apart from one study, there was no computer‐generated randomization or allocation concealment of the subjects doing different lung function tests, 39 leading to selection bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Permanent obstruction and impaired gas exchange mechanism in the airways that develop due to chronic inflammation and sputum cause the decrease of respiratory function and respiratory muscle strength 3,4 . Also, impairment of functional capacity and balance are extrapulmonary manifestations of NCFB 4,5 …”
Section: Introductionmentioning
confidence: 99%